Study on the effect of high energy ultrasonic wave on MIG welding deformation and welding joint performance of LC52 aluminum alloy plate - Cong Jin; Chunguang Xu; Peilu Li; Peng Yin; Yunxi Gao; Yongqiang Wang (Scientific Reports)
Abstract The analysis of MIG welding performance and welding deformation control of medium/high strength aluminum alloy plates is a hot topic of current research. By applying high-energy ultrasound during the MIG welding process to control the welding deformation and performance of welded joint of LC52 aluminum alloy plate, and comparing and analyzing it with the traditional MIG welded joint, the influence of high-energy ultrasound control process parameters on the welding residual stress distribution, welding deformation, mechanical properties, and microstructure of LC52 aluminum alloy welding test plate was mastered. The residual stress values and distribution state of high-energy ultrasonic welding compared with conventional welding were analyzed through the use of LCR wave stress detection method with conversion or broadband frequency. The microscopic grain structure of welded joint was studied by using metallographic optical microscopy, impact testing and tensile testing of welded joint were carried out and the fracture pattern of tensile specimens was observed by using scanning electron microscopy. The crystallization process of the welded joint was changed by injecting high-energy ultrasound in the MIG welding process, meanwhile, the process of weld solidification and heat transfer or diffusion based on the action of high-energy ultrasonic wave directly led to changes in the properties of the welded joint. The results showed that the welding residual stress was significantly reduced and homogenized in the MIG welding process of LC52 aluminum alloy plate based on certain timing constraints after the application of high-energy ultrasonic control. The average welding residual stress reduction rate and the stress homogenization rate of the plate under each detection depth reached more than 70.0% and 50.0%, respectively. The welding deformation was effectively controlled with reduction by 68.8%. In addition, the grain size and distribution state of microstructure in the weld zone, fusion and heat affected zone were refined and equalized by using this welding control process. Compared with the conventional welding method (i.e., not under regulation), the impact strength of the weld fusion and heat-affected zone under the action of high-energy ultrasonic waves were increased by 71.7% and 33.6%, respectively, and the tensile strength and elongation of the welded joint were increased by 24.0% and 46.7%, respectively, improving the fracture morphology of weld and then showing better mechanical properties. Therefore, the process of high-energy ultrasonic MIG welding was applied to control the welding deformation and improve the welding properties of LC52 aluminum alloy. The important support for improvement of the welding quality of aluminum alloy plate and even its stability and safety in service was provided by this study.